Virtual World as a Resource for Hybrid Education - Díaz, Jairo Eduardo Márquez; Saldaña, Camilo Andrés Domínguez; Ávila, Camilo Alberto Rodríguez (International journal of emerging technologies in learning, 2020)
The virtual worlds in the educational environment, have opened new possibilities to innovation in the teaching-learning process, where the flexibility of access to information inside or outside the classroom through an avatar, tends to a paradigm shift in education traditional, in terms of the way of transmitting and acquiring knowledge through technological means. In this sense, an investigation was carried out on the design, development and use of a metaverse as a digital tool of didactic support to students of the Faculty of Systems Engineering of the University of Cundinamarca, with a view to establishing its viability to be implemented in a course of mathematics and demonstrate the possibilities offered by this type of resource to motivate the student in his training. The metaverse design included various ICT tools, thereby promoting self-learning and collaborative learning. Finally, it was evaluated what was the appreciation of a group of students against their interaction with the metaverse, which validated its usefulness and functionality inside and outside the classroom.